Bacterial and fungal microbiota of spontaneously fermented Chinese products, Rubing milk cake and Yan-cai vegetable pickles. (June 2018) - Liu, Xin; Kuda, Takashi; Takahashi, Hajime; Kimura, Bon
Abstract: The Rubing milk cake from Yunnan and the Yan-cai vegetable pickles from Guangdong are traditional spontaneously fermented foods in China. We evaluated the microbial properties of these products with the analysis of their bacterial and fungal microbiota using classical culture-dependent and culture-independent methods, including a 16S rDNA gene (V4) and an internal transcribed spacer (ITS) region pyrosequencing method with MiSeq system. The viable lactic acid bacteria (LAB) count was 8 and 6 log colony-forming units (CFU)/g in Rubing and Yan-cai samples, respectively. The yeast count was approximately 100–1000 times less than the LAB count in most samples, except one Yan-cai sample. In addition, the gram-negative rod count in half of the samples was similar to the LAB count. Pyrosequencing results revealed the high abundance (10%–20%) of gram-negative Pseudomonas spp. and Enterobacteriaceae in these samples. These results suggest that some of these traditional foods are undesirable as ready-to-eat (RTE) foods, even when these are typical lactic acid fermented foods. Highlights: Rubing is a spontaneously fermented milk product made in Yunnan. Yan-cai is an spontaneously fermented vegetable pickle. Culture method showed high gram-negative rod counts in some samples. Contaminated samples showed high abundance of Enterobacteriaceae or Pseudomonas. To use as starters, stress-resistant LAB and yeast strains were isolated and identified.